Dapt Review - Özkan, KARACA; Mehdi, KARASU; A, KOBAT Mehmet; Tarık, KIVRAK (Journal of Cardiology and Cardiovascular Medicine, 2020)
Dual antiplatelet therapy (DAPT) combining aspirin and a P2Y12 receptor inhibitor has been consistently shown to reduce recurrent major adverse cardiovascular events (MACE) in patients with acute coronary syndrome (ACS) or undergoing percutaneous coronary intervention (PCI) for stable coronary artery disease (CAD) compared with aspirin monotherapy but at the expense of an increased risk of significant bleeding. Among patients with stable CAD undergoing PCI with drug-eluting stents (DES), shorter duration of DAPT (3–6 months) were shown non-inferior to 12 or 24 months duration concerning MACE but reduced the rates of major bleeding? Contrariwise, prolonged DAPT durations (18–48 months) reduced the incidence of myocardial infarction and stent thrombosis, but at the cost of an increased risk of majör bleeding and all-cause mortality. Until more evidence becomes available, the choice of optimal DAPT regimen and duration for patients with CAD requires a tailored approach based on the patient clinical presentation, baseline risk profile and management strategy. Patients with acute coronary syndromes (ACS) and a history of atrial fibrillation (AF) have indications for both dual antiplatelet therapy (DAPT) and oral anticoagulation (OAC). Triple therapy (TT), the combination of DAPT and OAC, is recommended in guidelines. This article provides a contemporary state-of-the-art review of the current evidence on DAPT for secondary prevention of patients with CAD and its future perspectives.